2015
DOI: 10.18632/oncotarget.6059
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27b, microRNA-101 and microRNA-128 inhibit angiogenesis by down-regulating vascular endothelial growth factor C expression in gastric cancers

Abstract: Vascular Endothelial Growth Factor C (VEGF-C) has critical roles in angiogenesis in human cancers; however, the underlying mechanisms regulating VEGF-C expression remain largely unknown. In the present study, VEGF-C protein expression and the density of blood vessels or lymphatic vessels were determined by immunohistochemistry in 103 cases of gastric cancer tissues. Suppression of VEGF-C by miR-27b, miR-101 and miR-128 was investigated by luciferase assays, Western blot and ELISA. The miRNAs expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 31 publications
4
49
0
Order By: Relevance
“…Accumulating evidence further indicates that numerous miRNAs can impede cancer progression via direct suppression of VEGF-C. The miRNAs miR-101, miR-128, miR-206 and miR-1826 have been reported to inhibit tumour growth, lymphangiogenesis and metastasis by targeting VEGF-C in a variety of human cancer cells [24][25][26][47][48][49]. The present study showed that adiponectin markedly repressed miR-27b expression in human chondrosarcoma cells in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 54%
“…Accumulating evidence further indicates that numerous miRNAs can impede cancer progression via direct suppression of VEGF-C. The miRNAs miR-101, miR-128, miR-206 and miR-1826 have been reported to inhibit tumour growth, lymphangiogenesis and metastasis by targeting VEGF-C in a variety of human cancer cells [24][25][26][47][48][49]. The present study showed that adiponectin markedly repressed miR-27b expression in human chondrosarcoma cells in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 54%
“…Deregulated biogenesis of miRNAs has been widely observed in human cancer [18]. Accumulating evidences further indicate that numerous miRNAs can impede cancer progression via direct suppression of VEGF-C. miR-27b, miR-101, miR-128, miR-206 and miR-1826 have been reported to inhibit tumor growth, lymphangiogenesis and metastasis by targeting VEGF-C in a variety of human cancer cells [2022, 3840]. Current study showed that CCL5 markedly repressed miR-507 expression in human chondrosarcoma cells in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression miR-27b reduces the proliferation, migration and tube formation of HUVECs and decreases angiogenesis in colorectal cancer and gastric cancer via inhibiting the VEGFC/VEGFR2 signalling. 147,148 Moreover, a recent study indicated that miR-27b effectively represses migration and tube formation of ovarian cancer cells, and angiogenesis in vivo by inhibiting VE-cadherin. 145 In the bladder, prostate and colon tumours, miR-27b plays anti-tumour and anti-angiogenesis roles.…”
Section: Mir-27bmentioning
confidence: 99%